WORK IN SMALL GROUPS WHEN TEACHING THE RUSSIAN LANGUAGE. (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article reveals the issues of organizing work in small groups - as one of the forms of cognitive activity of students when teaching the Russian language.